2017
DOI: 10.1016/j.radcr.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Calcifying aponeurotic fibroma in a girl: MRI findings and their chronological changes

Abstract: Calcifying aponeurotic fibroma (CAF) is a rare benign tumor that typically develops in the fascia and tendons. On MRI, CAF usually shows isointensity on T1WI and heterogeneous high intensity on T2WI. We report a case of 17-month-old girl with CAF on her right ankle. MRI showed an usual signal intensity for CAF. At 3 years and 4 months of age, MRI revealed hyperintense nodules on T1WI and T2WI inside of the CAF. These fatty areas corresponded to coarse calcified nodules on CT. Radiologists should be aware of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Enzinger and Weiss suggested that CAFs develop biphasically, with initial and late phases. In the initial phase, seen more frequently in young patients, the tumor has an infiltrative and destructive growth and often lacks calcification; while in the late phase the tumor is more compact and nodular and exhibits a more prominent degree of calcification and cartilage formation [ 4 , 5 , 8 , 13 , 18 ]. The standard of care for CAFs includes proper diagnosis and conservative surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Enzinger and Weiss suggested that CAFs develop biphasically, with initial and late phases. In the initial phase, seen more frequently in young patients, the tumor has an infiltrative and destructive growth and often lacks calcification; while in the late phase the tumor is more compact and nodular and exhibits a more prominent degree of calcification and cartilage formation [ 4 , 5 , 8 , 13 , 18 ]. The standard of care for CAFs includes proper diagnosis and conservative surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors who reported CAF included hemangioma, fibroma or fibromatosis, localized tenosynovial giant-cell tumor (GCT), soft-tissue chondroma, and less commonly soft-tissue sarcoma such as synovial sarcoma in differential diagnosis (9,10). Especially, localized tenosynovial GCT is associated intimately with the tendon sheath and may erode bone.…”
Section: Discussionmentioning
confidence: 99%
“…It has relatively characteristic MRI finding with well-defined, lobulated margins, uniform enhancement, heterogeneous hypointense signals associated with hemosiderin deposition and pressure erosion, but very rare calcifications. Also, it rarely occurs in children (9,10). A soft-tissue chondroma has a well-defined, lobulated, and diffuse calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Calcification is a typical feature but occurs at the late stage. 23 -Lipofibromatosis: predilection for the extremities, poorly marginated mass with hyperechoic areas, corresponding to fat. 22,24 Superficial fibromatosis found in adults are plantar fibromatosis and palmar fibromatosis.…”
Section: Superficial Fibromatosesmentioning
confidence: 99%